The impact of COVID-19 on farmers’ mental health: a case study of the UK - Rose, David Christian; Shortland, Faye; Hall, Jilly; Hurley, Paul D.; Little, Ruth; nye, Caroline; Lobley, Matt (Taylor and Francis, 2022)
Objectives In this paper, we use a UK case study to explore how the COVID-19 pandemic affected the mental health (emotional, psychological, social wellbeing) of farmers. We outline the drivers of poor farming mental health, the manifold impacts of the pandemic at a time of policy and environmental change, and identify lessons that can be learned to develop resilience in farming communities against future shocks. Methods We undertook a survey answered by 207 farmers across the UK, focusing on drivers of poor mental health and the effect of the COVID-19 pandemic. We also conducted 22 in-depth interviews with individuals in England, Scotland and Wales who provide mental health support to farmers. These explored how and why the COVID-19 pandemic affected the mental health of farmers. These interviews were supplemented by 93 survey responses from a similar group of support providers (UK-wide). Results We found that the pandemic exacerbated underlying drivers of poor mental health and wellbeing in farming communities. 67% of farmers surveyed reported feeling more stressed, 63% felt more anxious, 38% felt more depressed, and 12% felt more suicidal. The primary drivers of poor mental health identified by farmers during the pandemic were decreased social contact, issues with the general public on private land, and moving online for social events. Support providers also highlighted relationship and financial issues, illness, and government inspections as drivers of poor mental health. Some farmers, conversely, outlined positive impacts of the pandemic. Conclusion The COVID-19 pandemic is just one of many potential stressors associated with poor farming mental health and its impacts are likely to be long lasting and delayed. Multiple stressors affecting farmers at the same time can create a tipping point. Therefore, there is a need for long-term support and ongoing evaluation of the drivers of poor mental health in farming families.
Keywords: agriculture; COVID-19; farmer; mental health; wellbeing